PENINGKATAN HASIL BELAJAR KELAS VI DALAM MENENTUKAN VOLUM BANGUN RUANG MELALUI PENGGUNAAN ALAT PERAGA KUBUS SATUAN - Widayanti, Eni (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
Based on the learning outcomes of students during the pre-cycle at SD Negeri Kalibanteng Kidul 01 on Basic Competency, determining the volume of the average spatial structure of students' learning outcomes is still low, namely 64. This is a problem for teachers to improve learning outcomes in these Basic Competences. Efforts made through the use of unit cube teaching aids are expected to be able to improve learning outcomes in Basic Competence in determining the volume of geometric shapes. The formulation of the problem posed in this scientific paper reads